1409. Genomic Variation Among Respiratory Syncytial Viruses. (31st December 2020) - Anderson, Christopher S; Zhang, Yun; Corbett, Anthony; Chu, Chin-Yi; Wang, Lu; Qiu, Xing; McCall, Mathew; Topham, David; Mariani, Tom; Walsh, Edward E; Scheuermann, Richard; Caserta, Mary T
Abstract: Background: Respiratory Syncytial Virus (RSV) can be easily classified into two subtypes (A and B) based on the nucleic acid sequence of their genome. Phylogenic approaches have shown that within both subtypes separate lineages of viruses exist and new lineages continue to emerge. The role these genomic variations play in disease severity during RSV infection is largely unknown. Methods: Next-generation viral RNA sequencing was performed on archived frozen nasal swabs of children infected with RSV in Rochester, NY between 1977-1998. Genomic variation was compared across year-of-isolation, age of host, and inpatient/outpatient status of host. Local RSV genomic variation was compared to variation of publicly available sequences isolated from hosts residing in other parts of the world. Results: A and B subtypes demonstrated significant differences in the genetic sequence and primary-protein structure over time. G-protein was the most variable in both subtypes, but they differed in the number of unique genotypes detected. We found a significant association with disease severity (inpatient/outpatient status) and RSV phylogenetic topology, although the magnitude of the association differed by subtype. Variation in the primary protein structure of RSV viral proteins was also significantly associated with disease severity, but depended on which viral protein, and which subtype, was investigated. Lastly, local RSV genomic and protein-structure variation was similar to what was seen globally during this time period. Conclusion: Overall, both subtypes demonstrated significant genetic change over time and these changes were associated with disease severity. These results suggest that the genetic variability of RSV may affect RSV disease in humans. Disclosures: All Authors : No reported disclosures